Putting Our Shoulder to the Wheel: Current Understanding and Gaps in Nerve Ablation for Chronic Shoulder Pain. (23rd July 2021) - Eckmann, Maxim S; McCormick, Zachary L; Beal, Colby; Julia, Jonathan; Cheney, Cole W; Nagpal, Ameet S
Abstract: Shoulder pain is prevalent, burdensome, and functionally limiting, with diverse pathology and associated treatments. This narrative review provides a summary of relevant neuroanatomy, proposed ablation targets, safety and efficacy concerns for ablation targets, and current research gaps. Radiofrequency ablation (RFA) of peripheral sensory nerves is a well-established treatment for chronic joint and spine pain, but it is relatively nascent for shoulder pain. Cadaveric studies demonstrate the shoulder joint is innervated by articular branches of the suprascapular nerve, axillary nerve, lateral pectoral nerve, and upper and lower subscapular nerves. Shoulder articular branch RFA appears to be a safe and effective treatment for chronic shoulder pain, but there are currently no widely accepted protocols for ablation targets. There are also no randomized controlled trials (RCT) assessing safety and efficacy of proposed targets or the prognostic value of articular blocks. Future research studies should prioritize categorical data, use appropriate functional measures as primary endpoints, and would ideally include a large-scale RCT.